2015
DOI: 10.1111/dme.13011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary protein on postprandial blood glucose levels in individuals with Type 1 diabetes mellitus using intensive insulin therapy

Abstract: AimTo determine the effects of protein alone (independent of fat and carbohydrate) on postprandial glycaemia in individuals with Type 1 diabetes mellitus using intensive insulin therapy.MethodsParticipants with Type 1 diabetes mellitus aged 7–40 years consumed six 150 ml whey isolate protein drinks [0 g (control), 12.5, 25, 50, 75 and 100] and two 150 ml glucose drinks (10 and 20 g) without insulin, in randomized order over 8 days, 4 h after the evening meal. Continuous glucose monitoring was used to assess po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
108
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(123 citation statements)
references
References 23 publications
8
108
0
2
Order By: Relevance
“…Seven studies examining the effect of dietary protein on postprandial glycemia in 125 subjects with type 1 diabetes (range 8-33 subjects) were identified (5,8,11,13,(15)(16)(17). All studies kept carbohydrate content consistent, with six adding protein to the test meal, thereby concurrently increasing the energy content.…”
Section: Proteinmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven studies examining the effect of dietary protein on postprandial glycemia in 125 subjects with type 1 diabetes (range 8-33 subjects) were identified (5,8,11,13,(15)(16)(17). All studies kept carbohydrate content consistent, with six adding protein to the test meal, thereby concurrently increasing the energy content.…”
Section: Proteinmentioning
confidence: 99%
“…Paterson et al (13) was the only study examining the effect of protein only (in the absence of carbohydrates and fat) and found that the addition of 12.5-50 g protein did not significantly affect glycemia, although the addition of 75 and 100 g significantly increased glucose concentrations, reaching a peak at the conclusion of the 5-h study and causing an increase in glucose concentrations similar to that of 20 g carbohydrates given without insulin. These results suggest that protein has differential effects when consumed with and without carbohydrates.…”
Section: Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…Protein içeriği yüksek öğünlerin 2-5 saatlik postprandiyal periyotta daha yüksek glisemik seyre neden olduğu saptanmıştır. 5,13,23,27,28 Peters ve ark.nın ça-lışmasında, protein eklenmiş öğün sonrası erken glukoz yanıt standart öğün ile benzer bulunur iken, geç glukoz yanıtta artış gözlenmiştir. Ayrıca, protein eklenmiş öğün sonrası geç insülin ihtiyacı daha fazla bulunmuştur.…”
Section: Di̇yet Protei̇nleri̇ni̇n Postprandi̇yal Gli̇semi̇ üZeri̇ne Etki̇leri̇unclassified